Psychopathy among Mexican American Gang Members: A Comparative Study - Valdez, Avelardo (International journal of offender therapy and comparative criminology, 2000)
High-risk Mexican American males were assessed for levels of psychopathy. The Hare Psychopathy Checklist-Screening Version was compared in a random sample of gang members with a matched community sample of violent non-gang members and samples of forensic and psychiatric patients and undergraduate students. Analysis involved -test, chi- square, and Cronbach's alpha statistics. More than half of the gang sample were categorized as low, 44% as moderate, and only 4% as high on psychopathy. The gang members had higher scores on the total, affective, and behavioral scores than the non-gang members. High scores on adolescent antisocial behavior, poor behavioral controls, and lack of remorse were found in both samples. Gang members scored twice as high as non-gang members on lack of empathy. Both samples were lower on psychopathy than the forensics and higher than psychiatric patients and undergraduates. The results provide grounds for early intervention efforts for this high-risk population